Inhibitory effect of Newtonia extracts and myricetin-3-o-rhamnoside (myricitrin) on bacterial biofilm formation - Motlhatlego, Katlego E. (BMC Complement Med Ther, 2020)
BACKGROUND: Diarrhoea is a major health issue in both humans and animals and may be caused by bacterial, viral and fungal infections. Previous studies highlighted excellent activity of Newtonia buchananii and N. hildebrandtii leaf extracts against bacterial and fungal organisms related to diarrhoea-causing pathogens. The aim of this study was to isolate the compound(s) responsible for antimicrobial activity and to investigate efficacy of the extracts and purified compound against bacterial biofilms. METHODS: The acetone extract of N. buchananii leaf powder was separated by solvent-solvent partitioning into eight fractions, followed by bioassay-guided fractionation for isolation of antimicrobial compounds. Antibacterial activity testing was performed using a broth microdilution assay. The cytotoxicity was evaluated against Vero cells using a colorimetric MTT assay. A crystal violet method was employed to test the inhibitory effect of acetone, methanol: dichloromethane and water (cold and hot) extracts of N. buchananii and N. hildebrandtii leaves and the purified compound on biofilm formation of Pseudomonas aeruginosa, Escherichia coli, Salmonella Typhimurium, Enterococcus faecalis, Staphylococcus aureus and Bacillus cereus. RESULTS: Myricetin-3-o-rhamnoside (myricitrin) was isolated for the first time from N. buchananii. Myricitrin was active against B. cereus, E. coli and S. aureus (MIC = 62.5 μg/ml in all cases). Additionally, myricitrin had relatively low cytotoxicity with IC(50) = 104 μg/ml. Extracts of both plant species had stronger biofilm inhibitory activity against Gram-positive than Gram-negative bacteria. The most sensitive bacterial strains were E. faecalis and S. aureus. The cold and hot water leaf extracts of N. buchananii had antibacterial activity and were relatively non-cytotoxic with selectivity index values of 1.98–11.44. CONCLUSIONS: The purified compound, myricitrin, contributed to the activity of N. buchananii but it is likely that synergistic effects play a role in the antibacterial and antibiofilm efficacy of the plant extract. The cold and hot water leaf extracts of N. buchananii may be developed as potential antibacterial and antibiofilm agents in the natural treatment of gastrointestinal disorders including diarrhoea in both human and veterinary medicine.